The Teacher Development in Creating the Databases of Learning Resources and Local Wisdom for Enhancing the Instructional Quality - หมื่นแจ่ม สำเนา (Community and Social Development Journal, 2015)
The purposes of this research were 1) to develop the participating teachers in creating a learning resources database and a local wisdom database; and 2) to examine the effects of teacher development in enhancing the quality of teacher instruction. The research was conducted using an action research approach four stages : planning, action, observation and reflection. The target group herein was twenty-nine schoolteachers of Chonprathanpateak school. The informants were twenty students, fifteen parents, and fifteen skilled and knowledgeable locals. The research instruments were the forms of documentary analysis, brainstorming guidelines, teachers’ behavior observation, teacher and student interviews, pre-and-post test of attending the workshops, and teacher’s satisfaction questionnaire. The tools quality were proved by using including Index of Item - Objective. Congruence or IOC by educational experts .The statistic of the reliability of the test and the questionnaire using alpha coefficient (α-coefficient) of Cronbach. The quantitative data was analyzed by percentage, mean, standard deviation and the qualitative data was analyzed by content analysis. The descriptive approach was then employed to present its research findings. The research findings were summarized as follows: 1. To develop the participating teachers in creating a learning resources database and a local wisdom database included 13 activities as follows: 1)a workshop analyzing documents, and brainstorming in relation to examining what critical issues of problems and needs were tailored to teacher development using learning resources and local wisdom. 2)a workshop planed to make teacher development. 3)a workshop analyzed learning resources and local wisdom.4)a workshop analyzed curriculum were utilized in a learning resources and a local wisdom. 5) a workshop created a learning resources database and a local wisdom database. 6) a workshop determined the qualities of a learning resources database and a local wisdom database. 7) a workshop designed learning management units. 8) a workshop wrote learning management plans. 9) a researcher supervised learning management units and learning management plans. 10) a workshop determined the qualities of learning management units and learning management plans.11) a teachers who provided learning activities for the students. 12) a behavioral observations and supervision of the teachers were periodically undertaken in order to enquire what problems the teachers had encountered, to provide them with assistance in solving the existing issues in every aspect as well as with learning activit 13) a workshop was held to reflect the outcomes of learning management that were then reported to school administers and a committee of teachers as well. 2. The findings on the effects of teacher development in creating the databases of learning resources and local wisdom suggested that all the teachers had the knowledge and understanding of how to create the databases of learning resources and local wisdom. The average score after all the teachers had attended the workshops was 27.93 % higher than the average score before attending the workshops. They had the satisfaction of learning management towards the implementation of their learning resources database and local wisdom database in terms of teacher development activities with 4.56, database application with 4.54, learning management with 4.52, administration with 4.51, respectively. 3. The findings on learning management by the implementation of the learning resources database and local wisdom database suggested that the students had the learning achievement in all levels. Their scores were 24.56-40.03 % high. The students expressed their opinions that they had happiness and fun to learn from real-life experience to the gained knowledge and understandings; they took great pride and raised awareness of culture, traditions, learning resources and local wisdom in their community.